Biochemistry and molecular biology - William H Elliott (Oxford Univ. Press, 1997)
The book covers topics of current special interest as well as more traditional areas in biochemistry. There is an emphasis on biological aspects of biochemistry. As well as presenting core material on the structure of proteins and membranes, metabolism, and information storage and utilization, it also surveys the immune system, viruses and viroids, and the disparate enzymic protective mechanisms in the body.